Mechanics for Seedling Feeding in Vegetable Transplanters: Design and Development of Semi-Automatic Systems - Ankit Sharma; Sanjay Khar (Spanish Journal of Agricultural Research)
Aim of study: The seedling feeding mechanism is a significant element in transplanters. The current study designed and developed two semi-automatic mechanical seedling feeding mechanisms for the tractor mounted vegetable transplanter, revolving multi-chamber disc (FMRMD) and horizontal dragging magazines (FMHDM).